Tabori - ključna oblika učenja o dezinstitucionalizaciji - Cafuta Maček, Jošt (Socialno delo, 2025)
The article is based on a study practice carried out by students of the Faculty of Social Work, University of Ljubljana, in the 2015/16 academic year at three camps in Serbia, in three different institutions for people with mental health issues. It shows the connection between the democratic principles of deinstitutionalization and the need to introduce them into the higher education system. The emphasis is on a specific form of teaching and creating knowledge about, and for deinstitutionalization, at deinstitutionalization camps. Special attention is paid to the impact of camps on the process of deinstitutionalization and to camps as a method of teaching social work. It shows how insights into the democratization of relationships and knowledge creation in the community can also be used in the development of social work education.
Keywords: creation of knowledge; Deinstitucionalizacija; deinstitutionalisation; dezinstitucionalizacija; duševno zdravje; higher education; mental health; power relations; razmerja moči; social work; socialno delo; tabori; total institutions; totalne ustanove; ustvarjanje znanja; visoko šolstvo